2004
DOI: 10.1097/01.fjc.0000137161.76616.85
|View full text |Cite
|
Sign up to set email alerts
|

Nitric-Oxide Mediated Effects of Transdermal Capsaicin Patches on the Ischemic Threshold in Patients with Stable Coronary Disease

Abstract: Transdermal capsaicin may improve ischemic threshold in patients with stable coronary disease, probably through arteriolar vasodilation. Increased capsaicin-induced NO availability could represent the principal mechanism of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Cutaneous dilatation with transdermal use of capsaicin depends on age, gender and applied dose of capsaicin with young men being positive responders compared to older men; and women being non-responders (Munce and Kenney 2003;Ferrell et al, 2004) and no effect with repeated use (Roberts et al, 1992). Capsaicin significantly delays ST depression time during exercise test in male patients with stable coronary disease, indicating a possible role of capsaicin in arteriolar vasodilatation in men (Fragasso et al, 2004). Although there was no significant difference in the whole group, the resting heart rate was lower and SEVR (a measure of myocardial perfusion) was higher in men, after 4 weeks of regular chilli consumption.…”
Section: Glyceryl Trinitrate Salbutamolmentioning
confidence: 97%
“…Cutaneous dilatation with transdermal use of capsaicin depends on age, gender and applied dose of capsaicin with young men being positive responders compared to older men; and women being non-responders (Munce and Kenney 2003;Ferrell et al, 2004) and no effect with repeated use (Roberts et al, 1992). Capsaicin significantly delays ST depression time during exercise test in male patients with stable coronary disease, indicating a possible role of capsaicin in arteriolar vasodilatation in men (Fragasso et al, 2004). Although there was no significant difference in the whole group, the resting heart rate was lower and SEVR (a measure of myocardial perfusion) was higher in men, after 4 weeks of regular chilli consumption.…”
Section: Glyceryl Trinitrate Salbutamolmentioning
confidence: 97%
“…However, these studies did not distinguish between a direct action of capsaicin on endothelial TRPV1 as opposed to vascular effects secondary to nerve activation. Transdermal application of capsaicin improves the ischemic threshold in patients with coronary artery disease, and this benefit is related to the augmented plasma levels of NO and thus improved arteriolar vasodilatation, events unrelated to a change in the plasma concentration of CGRP (Fragasso et al, 2004). The present study shows that short-term dietary capsaicin did not affect blood pressure, the endothelium-dependent relaxation, and PKA/eNOS phosphorylation in mesenteric arteries of SHR.…”
Section: Discussionmentioning
confidence: 99%
“…Transdermal administration of capsaicin improves the ischemic threshold in patients with stable coronary disease. 38 Our previous studies showed that TRPV1 activation by dietary capsaicin alleviates metabolic disorders and attenuates aortic atherosclerosis as well as hypertension. 21,33,39,40 In this study, we further demonstrated that chronic dietary capsaicin supplementation ameliorated HFDinduced endothelial dysfunction in the coronary arteries and prolonged the lifespan of ApoE −/− receiving HFD.…”
Section: Trpv1 Activation Antagonizes Ros-mediated Coronary Lesions Bmentioning
confidence: 99%